Ambientes externos de aprendizaje, para el desarrollo psicomotriz de los niños y niñas que asisten al centro de educación inicial Mercedes de Jesús Molina de la ciudad de Riobamba en el año lectivo 2010- 2011. - Bravo Alcocer, Adriana (2011)
This research was conducted in order to demonstrate that external learning environments involved in the psychomotor development of children in the Early Education Center "Mercedes de Jesus Molina" in the city of Riobamba. Outer space not being conditioned confines the integral development of children considering the movement as a means of communication. For this study we have used the site investigation, field research, describing in a systematic way the state of the external spaces, as well as for improving psychomotor development of children. Used for the purpose of research which is applied within that served to solve an obvious problem, with the support was achieved Parents identify and bring security to the nursery area. We use the investigation into the level that is part of the descriptive. The population was involved in the investigation were: the Director, the Teacher, a Technical Support, 42 parents, 42 children. The instruments used for quality reporting were the interview, survey, observation guide, all to demonstrate the state of the external spaces. Tabulation and analysis was performed to calculate frequencies and percentages, the same as those plotted in pastels, giving the respective qualitative and quantitative interpretation, so drawing conclusions and recommendations. To solve the problem was delineated an area of 130 m2 exclusive early education, making a mesh enclosure and rags, grass is also placed for the comfort and drew up a tunnel with wheels supported by mingas parent. With determination and creativity can play as important needs without being unreasonable charges, for which we have begun the first step as an example that if you can, to continue in this process will assist the institution with various alternative development recreational games with environmental materials